Assessing soil compaction and micro-topography impacts of alternative heather cutting as compared to burning as part of grouse moor management on blanket bog - Heinemeyer, Andreas; Berry, Rebecca; Sloan, Thomas J. (PeerJ, 2019)
Background Over 25% of the UK land area is covered by uplands, the bulk of which are comprised of blanket bog. This not only contains most of the UK’s terrestrial carbon stocks, but also represents 15% of this globally rare habitat. About 30% of UK blanket bog is managed for red grouse by encouraging ling heather (Calluna vulgaris) with rotational burning, which has been linked to habitat degradation, with reduced carbon storage and negative impacts on water storage and quality. Alternative cutting is currently being pursued as a potential restoration management. However, the often used heavy cutting machinery could cause considerable compaction and damage to the peat surface. Two particular issues are (i) a potential increase in bulk density reducing water storage capacity (i.e., less pore volume and peat depth), and (ii) a possible reduction of the micro-topography due to cutting off the tops of hummocks (i.e., protruding clumps or tussocks of sedges). Methods We set up a fully replicated field experiment assessing cutting versus burn management impacts on peat physical and surface properties. Both managements reflected commonly used grouse moor management practice with cutting using heavy tractors fitted with load distributing double wheel and tracks (lowering ground pressure), whilst burning was done manually (setting heather areas alight with flame torches). We assessed management impacts on peat depth, bulk density and peat surface micro-topography which either included pre-management measurements or plot-level data for uncut plots. Total peat depth and bulk density in four 5 cm sections within the top 50 cm was assessed. Micro-topography was determined as the standard deviation of the height offsets measured over several plot transects in relation to the plot peat surface level at the start and end points of each transect. Results Despite an anticipated compaction from the heavy machinery used for cutting, the peat showed resilience and there was no lasting plot-level impact on either peat depth or bulk density. Notably, bulk density showed differences prior to, and thus unrelated to, management, and an overall increasing bulk density, even in uncut plots. However, cutting did reduce the plot micro-topography by about 2 cm, mostly due to removing the tops of hummocks, whereas burnt plots did not differ from uncut plots. Discussion Cutting is suggested as a suitable alternative to burning on grouse moors, although compaction issues might be site specific, depending on the nature of the peat, the machinery used and impacts at resting and turning points (which were not assessed). However, any observed bulk density differences could reflect natural changes in relation to changes in peat moisture, requiring adequate experimental comparisons. Moreover, where micro-topography is a priority, cutting equipment might need to consider the specific ground conditions, which could involve adjusting cutting height and the type of cutting machinery used.
Keywords: Peatland; Soil compaction; Bulk density; Mowing; Burning; Micro-topography; Heather management; Blanket bog; Peat surface